A Digest of the Laws of the State of Georgia. From Its First Establishment as a British Province Down to the Year 1798 . . ., at 153-54 (1800) - (:unkn) unknown (General Publisher, 1768)
Prohibited “any slave” from possessing firearms, ammunition, or weapons without a ticket from their master or a white person over the age of sixteen present and any time after sunset on Saturday but before sunrise Monday morning.
--
Keywords: ENSLAVED PERSONS & OTHER MINORITIES